2004
DOI: 10.1080/00029157.2004.10403613
|View full text |Cite
|
Sign up to set email alerts
|

Self-Hypnosis Relapse Prevention Training with Chronic Drug/Alcohol Users: Effects on Self-Esteem, Affect, and Relapse

Abstract: This study evaluated the effectiveness of a self-hypnosis protocol with chronic drug and alcohol patients in increasing self-esteem, improving affect, and preventing relapse against a control, a transtheoretical cognitive-behavioral (TCB), and a stress management (attention-placebo) group. Participants were 261 veterans admitted to Substance Abuse Residential Rehabilitation Treatment Programs (SARRTPs). Participants were assessed pre- and postintervention, and at 7-week follow-up. Relapse rates did not signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…While the use of hypnosis has been investigated in a large number of RCTs in smoking cessation, only one RCT of its use in abstinence from substance use has been published (Pekala et al, 2004). While the use of hypnosis has been investigated in a large number of RCTs in smoking cessation, only one RCT of its use in abstinence from substance use has been published (Pekala et al, 2004).…”
Section: Hypnosis and Substance Use Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…While the use of hypnosis has been investigated in a large number of RCTs in smoking cessation, only one RCT of its use in abstinence from substance use has been published (Pekala et al, 2004). While the use of hypnosis has been investigated in a large number of RCTs in smoking cessation, only one RCT of its use in abstinence from substance use has been published (Pekala et al, 2004).…”
Section: Hypnosis and Substance Use Disordersmentioning
confidence: 99%
“…Relapse was assessed at the end of the intervention and again at 7 weeks where no difference was found between groups (Pekala et al, 2004). Study interventions involved the provision of four 1-h sessions.…”
Section: Hypnosis and Substance Use Disordersmentioning
confidence: 99%
“…Participants from two AOD treatment units within which they were matriculated, and as part of a study on relapse prevention (reported elsewhere, Pekala et al, 2004), completed a variety of questionnaires upon matriculation in the study. These included the SSES, SOCRATES, and RAI.…”
Section: Methodsmentioning
confidence: 99%
“…Although AA and NA (Alcoholics Anonymous, 1976;Nace, 1992) attempt to foster serenity through participation in self-help groups and alignment with a spiritual perspective and readings associated with AA/NA, interventions targeting the fostering of serenity via training protocols such as self-hypnosis training (Pekala et al, 2004), meditation (Kabat-Zinn, 2003), prayer (Zeiders & Pekala, 1995), pranayama (Iyengar, 1981), and related practices may also be important avenues for future research.…”
Section: Serenity Anger/impulsivity and Self-esteemmentioning
confidence: 98%
“…The most recent and well-designed study included three control groups: attention-placebo (stress management), cognitive-behavioural trans-theoretical intervention and no additional intervention group (Pekala et al, 2004). The abstinence rate in all groups was between 85 and 90% at two-month follow-up.…”
Section: Introductionmentioning
confidence: 99%